A Clinical Pilot Study Comparing Sweet Bee Venom parallel treatment with only Acupuncture Treatment in patient diagnosed with lumbar spine sprain - Shin Yong-jeen (Korean Pharmacopuncture Institute, 2011)
Objectives: This study was carried out to compare the Sweet Bee Venom (referred to as Sweet BV hereafter) acupuncture parallel treatment to treatment with acupuncture only for the patient diagnosed with lumbar spine sprain and find a better treatment. Methods: The subjects were patients diagnosed with lumbar spine sprain and hospitalized at Suncheon oriental medical hospital, which was randomly divided into sweet BV parallel treatment group and acupuncture-only group, and other treatment conditions were maintained the same. Then,VAS (Visual Analogue Scale) was used to compare the difference in the treatment period between the two groups from VAS 10 to VAS 0, from VAS 10 to VAS 5, and from VAS 5 to VAS 0. Result & Conclusion: Sweet BV parallel treatment group and acupuncture-only treatment group were compared regarding the respective treatment period, and as the result, the treatment period from VAS 10 to VAS 5 was significantly reduced in sweet BV parallel treatment group compared to the acupuncture-only treatment group, but the treatment period from VAS 5 to VAS 0 did not show a significant difference. Therefore, it can be said that sweet BV parallel treatment is effective in shortening the treatment period and controlling early pain compared to acupuncture-only treatment.